Tinjauan Pengaruh Lingkungan Kerja, Disiplin Kerja, Tekanan Kerja dan Kompensasi terhadap Kinerja Karyawan pada PT Tolan Tiga Indonesia Perlabian Estate - Esha Khulin; Siti Lam’ah; Daslan Simanjuntak (Fakultas Ekonomi Universitas 45 Surabaya, 2024)
This study aims to analyze the effect of work environment, work discipline, work pressure, and compensation on employee performance at PT Tolan Tiga Indonesia. The research method used is a quantitative approach with multiple linear regression analysis techniques. The sample used was 63 respondents who were the entire employee population. The results showed that simultaneously the four independent variables had a significant effect on employee performance, with a coefficient of determination (R²) value of 0.727, which means that 72.7% of performance variations can be explained by these variables. However, partially, only work discipline, work pressure and compensation have a significant effect on employee performance. An interesting finding is that work pressure has a significant positive effect, which indicates the existence of eustress-work pressure that actually motivates employees to work more effectively. In contrast, the work environment did not show a significant effect, which is suspected because both already meet the minimum standards of the organization. This study suggests that management should focus more attention on managing work pressure and improving a fair compensation system to encourage optimal productivity.